POLA KOMUNIKASI ANTAR PRIBADI MAHASISWA PAPUA DILINGKUNGAN UNIVERSITAS BENGKULU - Sabarhati Menderita Lumban Gaol; Dedi Supriadi; Khairil Khairil (Professional: Jurnal Komunikasi dan Administrasi Publik, 2020)
This study aims to determine the interpersonal communication patterns of Papuan students who study at the University of Bengkulu. This study aims to explain more deeply the patterns of verbal and non- verbal communication between Papuan students through an in-depth interview process. The method used in this study is a qualitative descriptive method using De Vito's Theory (Humanistic Approach). The technique of collecting data is by conducting observations, in-depth interviews, and documentation. The results of this study indicate that Papuan students feel intimidated by the behavior they receive, this is the motive why Papuan students are rarely involved in social interaction and make distance between them and Bengkulu students, namely general distance because they feel insecure and uncomfortable when around Bengkulu students. Keywords: communication patterns, interpersonal communication, papuan students, de vito's theory, campus environment